1000 'when you hear hoofbeats...'. (1st December 2017) - Sumangala, Salini; Nikfekr, Esmaeil; George, Jithin; Holmes, Christopher
Abstract : Leprosy is an uncommon disease in England and Wales, yet it remains an important disease globally with 2 50 000 cases diagnosed annually. Underreporting is likely in developed countries, where awareness of the clinical phenotypes and presentations of the disease may be lower than in higher prevalence countries. A 44 year old gentleman of Indian origin presented with swollen left forearm and erythematous plaque on the left hand. Clinical assessment revealed wasting of intrinsic muscles in the hypothenar eminence, profound motor and sensory deficit in the ulnar nerve distribution, with clawing of 4th and 5th digits of the left hand. EMG showed complete denervation of the left ulnar nerve. A modified Ziehl-Neelsen stain of the left arm skin biopsy demonstrated numerous, small aggregate bacilli, frequently co-localised within the areas of granulomatous inflammation. The skin biopsy sample identified the presence of bacterial 16 s DNA. Further analysis with 16S DNA sequencing was specific for Mycobacterium Leprae, thereby confirming the diagnosis of leprosy neuropathy.